Using Think-Alouds to Examine Reader-Text Interest - Wade, Suzanne E.; Buxton, William M.; Kelly, Michelle (Reading research quarterly, 1999)
Using multiple measures, this two-part investigation examined what text characteristics readers considered interesting and uninteresting, the relationships among these text characteristics, and how interest affected recall in two different expository texts on a high-interest topic--dinosaurs. Based on think-alouds and postreading verbal reports of college students in the first experiment, five text characteristics were most associated with interest: (a) information that was important, new, and valued; (b) information that was unexpected; (c) connections readers made between the text and their prior knowledge or experience; (d) imagery and descriptive language; and (e) authors connections (e.g., comparisons and analogies). Characteristics that made the texts uninteresting involved problems related to comprehension--specifically, lack of adequate explanation and background information, difficult vocabulary, and lack of coherence. In addition, lack of credibility interfered with the value of the new information and theories presented in the texts. In the second experiment, rating results indicated that interest and importance were highly correlated. In recall, a statistically significant interaction was found between interest and importance, with information rated as both interesting and important recalled best. Results are discussed in terms of the theoretical and empirical literature on interest, with implications for curriculum development and research. /// [Spanish] En esta investigación, que comprende dos experimentos, se usaron varias medidas para examinar las características de textos que resultaron interesantes y poco interesantes a los lectores, las relaciones entre estas características textuales y la forma en que el interés afectó el recuerdo de dos textos expositivos diferentes acerca de un tema de gran interés: los dinosaurios. En el primer experimento, basado en protocolos de pensamiento en voz alta y relatos posteriores a la lectura hechos por estudiantes universitarios, se encontraron cinco características textuales muy asociadas al interés: (a) información importante, nueva y valorada, (b) información inesperada, (c) conexiones entre el texto y el conocimiento previo o experiencia de los lectores, (d) lenguaje imaginativo/descriptivo y (e) conexiones hechas por los autores (e.g., comparaciones y analogías). Las características de los textos poco interesantes consistieron en problemas relacionados con la comprensión, específicamente la falta de explicación adecuada e información previa, un vocabulario difícil y la falta de coherencia. Además, la falta de credibilidad interfirió con el valor de la información nueva y las teorías presentadas en los textos. En el segundo experimento, se observó una correlación alta entre el interés y la importancia. En los relatos, se halló una interacción estadísticamente significativa entre interés e importancia, la información evaluada como interesante e importante fue mejor recordada. Se discuten los resultados en términos de la literatura teórica y empírica sobre el interés, con implicancias para el diseño curricular y la investigación. /// [German] Durch das Anwenden verschiedener Maßstäbe erforschte diese zweiteilige Untersuchung die Textcharakteristiken welche die Leser als interessant und uninteressant empfinden, die Zusammenhänge zwischen diesen Textcharakteristiken, und wie sich dieses Interesse auf die Wiederholung von zwei ausgesuchten verschiedenen Texten über ein hochinteressantes Thema--Dinosaurier--auswirkt. Basierend auf lautes Denken und Nachlesen der mündlichen Berichte von Hochschulstudenten beim ersten Experiment wurden fünf Textcharakteristiken hauptsächlich mit folgenden Interessen assoziiert: (a) als wichtig hingenommene, neue, und wertvolle Informationen; (b) Information welche nicht erwartet wurde; (c) Verbindungen, welche die Leser zwischen dem Text und ihren Vorkenntnissen oder Erfahrungen machten; (d) imaginäre/darstellerische Sprache; und (e) Verbindungen zu Autoren (z.B. Vergleiche und Analogien). Charakteristiken, die den Text uninteressant erscheinen ließen, bestanden aus Problemen in Bezug auf Verstehen und Erfassen, speziell der Mangel an ausreichender Erklärung und Hintergrundinformationen, schwieriges Vokabular und mangelnder Klarheit [Kohärenz]. Ergänzend beeinträchtigte ein Mangel an Glaubwürdigkeit den Wert der in den Texten unterbreiteten neuen Informationen und Theorien. In dem zweiten Experiment wiesen die Bewertungsergebnisse daraufhin, daß Interesse und Wichtigkeit in einem hochgradigen Zusammenhang standen. In Rückschau wurde statistisch ein bedeutenderes Zusammenspiel zwischen Interesse und Wichtignahme bzw. Wesentlichkeit festgestellt, mit am besten erinnerten Informationen, die sowohl als beides--interessant und wesentlich--eingestuft wurden. Ergebnisse werden im Rahmen der theoretischen und empirischen Literatur je nach Interesse diskutiert, mit Implikationen für Lehrplanentwicklung und Forschung. /// [French] En utilisant de multiples mesures, cette investigation en deux parties a examiné quelles caractéristiques du texte les lecteurs jugent intéressantes et inintéressantes, les relations entre ces caractéristiques textuelles, et comment l'intérêt affecte le rappel dans deux textes informatifs différents portant sur un thème d'un grand intérêt, les dinosaures. En se basant sur des verbalisations de la pensée et des rapports verbaux post-expérimentaux d'étudiants de premier cycle dans la première expérience, on a trouvé cinq caractéristiques textuelles très associées à l'intérêt: a) une information importante, nouvelle, et valorisée; b) une information inattendue; c) des mises en rapport faites par le lecteur entre le texte et ses connaissances ou expériences antérieures; d) un langage imagé/descriptif; et e) des mises en rapport faites par les auteurs (par exemple, des comparaisons et des analogies). Les caractéristiques qui rendent les textes inintéressants incluent des problèmes liés à la compréhension, spécifiquement, un défaut d'explication adéquate et d'information de base, un vocabulaire difficile, et un manque de cohérence. De plus, le manque de crédibilité interfère avec la valeur de l'information nouvelle et les théories présentées dans les textes. Dans la seconde expérience, les échelles d'évaluation indiquent que l'intérêt et l'importance sont fortement corrélés. Dans le rappel, on a trouvé une interaction statistiquement significative entre l'intérêt et l'importance, l'information jugée à la fois intéressante et importante étant mieux rappelée. On discute les résultats en fonction de la littérature théorique et empirique relative à l'intérêt, et des implications pour l'évolution des programmes scolaires et de la recherche.